PENGARUH BERBAGAI DOSIS PUPUK KOMPOS ECENG GONDOK DAN PUPUK HIJAU Azolla microphylla TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Rissa Tri Ismayanti; Eny Fuskhah; Sutarno Sutarno (BUANA SAINS, 2020)
The aim of the study was to know the influence of the interaction of water hyacinth compost doses and Azolla microphylla green fertilizer doses on the growth and production of pakcoy. The research was conducted in the greenhouse and plant ecology and production laboratory of the Faculty of Animal Science and Agriculture, Diponegoro University, Semarang, Central Java. The study was conducted in January to March 2020. The experimental design of this research was Completely Randomize Design (CRD) 5 x 3 factorial pattern design with 3 replications. The first factor consists of 5 levels, namely without fertilizer, inorganic fertilizer (NPK), 50% recommendation of water hyacinth compost doses, 100% recommendation of water hyacinth compost doses, and 150% recommendation of water hyacinth compost doses. The second factor consists of 3 levels, namely without fertilizer, 50% recommendation of Azolla microphylla green fertilizer doses, and 100% recommendation of Azolla microphylla green fertilizer doses. The observed parameters were plant height, number of leaves, crown wet weight, and the production of the crown’s dry matter. Analyzing the data use variance analysis and Duncan’s multiple range test of 5% level. The results showed that there was an interaction between the treatment doses of water hyacinth compost and Azolla microphylla green fertilizer on plant height, number of leaves, crown wet weight, and the production of the crown’s dry matter. The treatment of 100% recommendation of water hyacinth compost doses (138 kg N/ha) and 100% recommendation of Azolla microphylla green fertilizer doses (138 kg N/ha) gave the best results than other treatments. The treatment of 100% recommendation of water hyacinth compost doses (138 kg N/ha) without the addition of Azolla microphylla green fertilizer as the same as the contribution of inorganic fertilizer that had done for once during cultivation to increasing the crown wet weight.